Penerapan Model Pembelajaran Visualization, Auditory, Kinesthetic Terhadap Kemampuan Penalaran Matematis Siswa Smp - Mariyam, Mariyam; Wahyuni, Rika; Setiawan, Muhammad Andre (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2019)
AbstractThis study aims to determine the mathematical reasoning abilities, activities and motivation of students by applying the Visualization Auditory Kinesthetic (VAK) learning model. This type of experimental research with the design of the Nonequivalent Pretest-Posttest Control Group Design. The experimental and control classes were given a pretest and a posttest to see the difference in improvement between the two. The population in this study were students of class VIII and the sample was not chosen purely randomly, namely by cluster random sampling (random class) and two classes were chosen. Data analysis using statistical tests namely Mann Whutney U-Test and descriptive analysis in the form of a percentage formula and the average score. The results of data analysis show that: (1) There is a difference in the increase in students' mathematical reasoning abilities, and the increase in the experimental class is higher than the control class; (2) Student learning activities in each indicator are in the very high category and the overall average is 88.075%; (3) The average student motivation in each indicator is in the high category and the overall student average is 4.00.Keywords: Visualization Auditory Kinesthetic, Reasoning, Activity, Motivation